Pengaruh Kompensasi, Motivasi Karyawan, dan Komitmen Organisasi Terhadap Kinerja Karyawan - Sondang Mariani Rajagukguk; Frisca Sylia Intan (Universitas Kristen Maranatha, 2017)
AbstractThis research examined the effect of compensation, employees motivation and organizational commitment to employees’ performance at PT Telkom Indonesia Tbk. Bandung. This study took samples of 56 out of the 146 employees at PT Telkom Indonesia Tbk. Bandung from the Division of Resources Management. Data collected through reviewing literature and field observations such as the distribution of questionnaires. Meanwhile, the sampling technique was done by using purposive sampling method. The test’s results of using multiple regression partially (t test) showed that compensation (X1) had influence on the performance, motivation (X2) did not affect the performance, and organizational commitment (X3) had influence on the performance (Y). While simultaneously (F test) showed that there was an influence between X and Y. Result of the coefficient of determination showed that th e independent variables are compensation, motivation, and organizational commitment simultaneous effect was 37.2% on performance. Keywords: Compensation, Employees Motivation, Employees Performance, and Organizational Commitment